The Egg Quality Characteristics of Layers Fed Varying Dietary Inclusions of Siam Weed (Chromolaena odorata) Leaf Meal (SWLM) - Fasuyi, A.O.; Fajemilehin, S.O.K.; Omojola, A.B. (International Journal of Poultry Science, 2005)
Twenty-four layers in their eighth month in lay were used to study the effects of dietary inclusion of Siam weed (chromolaena odorata) leaf meal (SWLM) on egg quality characteristics. SWLM was incorporated into the diets at 0%, 2.5% 5.0% and 7.5% in diets 1, 2, 3 and 4 respectively. Total egg production and total feed intake increased up to 5% level (diet 3) of inclusion after which there was a decline. The highest hen-day production (%) was obtained for diet 3 with the 5% inclusion. The control diet 1 had the best feed efficiency value. The average egg weight was not negatively affected by the treatment levels of SWLM. The average shell thickness slightly but insignificantly increased (P=0.05) with the increasing introduction of SWLM in the diets. The yolk colour score gave highly significant statistical differences ( P < 0.05) among treatment means in proportion to the dietary inclusion of SWLM. The albumen height showed a proportionate increase up to 5% level of SWLM inclusion before a decrease. The Haugh`s unit was also best at the 5% dietary inclusion level of SWLM. It can therefore be concluded at the level of this study that SWLM would probably not result in mortality as previously envisaged and can be included up to 5% level in the diets of laying hens with desirable aesthetic effect on egg yolk colouration.